1993
DOI: 10.3109/01485019308988363
|View full text |Cite
|
Sign up to set email alerts
|

Transferrin Concentration in Seminal Plasma with Special Reference to Serum Hormone Levels in Infertile Men

Abstract: The concentration of transferrin in seminal plasma and serum levels of LH, FSH, testosterone, and prolactin were measured in 94 male patients attending our infertility clinic. The concentration of transferrin in patients with azoospermia was lowest among azoospermia, oligozoospermia, and normozoospermia groups. There was significant positive correlation between the concentration of transferrin in seminal plasma and sperm density. However, seminal plasma transferrin was inversely correlated with serum levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Using transferrin immunolabeling 30,70 we showed that left-sided varicocele caused a decrease in both global and VII/VIII stage-specific transferrin in rats, indicating a functional alteration in the Sertoli cell. Under normal conditions, transferrin mRNA levels vary twofold across the complete cycle, being high during the stages XII to XIV and achieving its maximum at stages VII and VIII.…”
Section: Discussionmentioning
confidence: 89%
“…Using transferrin immunolabeling 30,70 we showed that left-sided varicocele caused a decrease in both global and VII/VIII stage-specific transferrin in rats, indicating a functional alteration in the Sertoli cell. Under normal conditions, transferrin mRNA levels vary twofold across the complete cycle, being high during the stages XII to XIV and achieving its maximum at stages VII and VIII.…”
Section: Discussionmentioning
confidence: 89%
“…In the present study there was no relationship (P > 0.05) between ST levels and hormones (Table 2) which is corroborated by studies of Fuse (8) and Ber (9). However, there are studies that show as Tfs was inversely correlated with serum levels of LH, FSH and prolactin (10,11). ST levels found were significantly lower in the cases in relation to control in agreement with previous studies conducted by different researchers in non-uremic populations with suspected sub/infertility.…”
Section: Discussionmentioning
confidence: 99%